1993
DOI: 10.1007/bf00206147
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting the thickness of the cervical prevertebral soft tissues

Abstract: Lateral cervical spine films of 227 patients examined over 2 years were analyzed to determine the thickness of the soft tissues anterior to C2 through C4. These measurements were correlated with patient age, sex, weight, shoulder width, neck width, and calculated radiographic magnification. We found that only patient weight and age had any statistically significant effect on the soft tissue thickness. A stepwise regression model produced a simple equation for predicting the mean value of the soft tissue thickn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

1995
1995
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 11 publications
0
13
0
Order By: Relevance
“…Assessment of the PVST thickness is the most commonly used method to evaluate for PVST edema and/or hematoma, which may accompany osseous or ligamentous injury. Several authors have calculated the average and normal upper limits for thickness of the PVST on lateral cervical spine radiographs [13][14][15][16][17][18][19] as published in Keats' and Sistrom's Atlas of Radiographic Measurement. 11 With the advent of MDCT as the initial radiologic evaluation of the cervical spine in the setting of suggested trauma, normal PVST measurements specific to that technique are essential.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Assessment of the PVST thickness is the most commonly used method to evaluate for PVST edema and/or hematoma, which may accompany osseous or ligamentous injury. Several authors have calculated the average and normal upper limits for thickness of the PVST on lateral cervical spine radiographs [13][14][15][16][17][18][19] as published in Keats' and Sistrom's Atlas of Radiographic Measurement. 11 With the advent of MDCT as the initial radiologic evaluation of the cervical spine in the setting of suggested trauma, normal PVST measurements specific to that technique are essential.…”
Section: Discussionmentioning
confidence: 99%
“…25 This could be explained by differences in a patient's body habitus, because patient weight has been shown to relate proportionally to the thickness of the PVST on radiographs. 26,27 In some patients, this fat plane can be identified more easily on parasagittal images due to relative thinning of this fat attenuation stripe in the midsagittal plane.…”
Section: Normal Appearance Of the Pvstmentioning
confidence: 99%
“…1 Although soft tissue swelling on X-ray has been referred to as an aid in identifying injury, 1,2 published measurement methods and recommendations on what constitutes swelling vary, as does the diagnostic significance of said swelling. [3][4][5][6][7][8][9][10][11][12][13][14][15][16] Measurements in millimetres (mm) may not be applicable across wide age ranges and an alternative is measurement as a ratio of vertebral body width. Some published normal values are based on primary evidence, but many statements regarding measurement norms are uncited, or citations do not correctly support the measurement.…”
Section: Introductionmentioning
confidence: 99%
“…Some published normal values are based on primary evidence, but many statements regarding measurement norms are uncited, or citations do not correctly support the measurement. [3][4][5][6][7][8][9][10][11][12][13][14][15] Table I provides a summary of published normal values.…”
Section: Introductionmentioning
confidence: 99%
“…Sistrom 14 found patients older than 70 years had smaller prevertebral soft tissue width. While, in the study from Mullin, comparison of the group of mean prevertebral soft tissue width revealed a marked increase in the groups that included patients 41 years and older.…”
Section: Discussionmentioning
confidence: 99%